2020
DOI: 10.3390/s20174712
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated IoT Architecture for Smart Metering Using Next Generation Sensor for Water Management Based on LoRaWAN Technology: A Pilot Study

Abstract: This pilot study focuses on the design, implementation, optimization and verification of a novel solution of smart measuring of water consumption and crisis detection leading to a smart water management platform. The system implemented consists of a modular IoT platform based on a PCB (Printed Circuit Board) design using the M2.COM standard, a LoraWAN modem and a LoraWAN gateway based on the Raspberry Pi platform. The prototype is modular, low-cost, low-power, low-complex and it fully reflects the requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…In this case, the most important aspect is the design of the network, i.e., specifying beforehand where the sensors should be deployed for an optimal monitoring, paying special attention to providing a good coverage of the monitored area and to guaranteeing connectivity of the wireless nodes. Static WSNs are heavily used in smart city scenarios as they are well-suited for smart metering of public services networks such as water and sewage [ 33 , 34 ], public lighting [ 35 ], parking [ 36 ] or traffic monitoring [ 37 , 38 , 39 ], as well as for generating the baseline monitoring of the city environment [ 38 , 39 ].…”
Section: Key Technologies Developedmentioning
confidence: 99%
“…In this case, the most important aspect is the design of the network, i.e., specifying beforehand where the sensors should be deployed for an optimal monitoring, paying special attention to providing a good coverage of the monitored area and to guaranteeing connectivity of the wireless nodes. Static WSNs are heavily used in smart city scenarios as they are well-suited for smart metering of public services networks such as water and sewage [ 33 , 34 ], public lighting [ 35 ], parking [ 36 ] or traffic monitoring [ 37 , 38 , 39 ], as well as for generating the baseline monitoring of the city environment [ 38 , 39 ].…”
Section: Key Technologies Developedmentioning
confidence: 99%
“…+++ [53,54] Interoperability It is the ability of systems to exchange information of unambiguous meaning. +++ [55,56] Smart product…”
Section: Name Description Effect On Optimization Examplesmentioning
confidence: 99%
“…To develop a smart water meter with leak-detection capabilities, the author of [14] used a set of simple sensors, mainly flow meters, to gather information about water flow in pipes, sending that information to a cloud system using LoRaWAN. To detect the presence of leaks, a simple comparison of adjutant sensors is performed, classifying a possible leak based on the drop of flow between those two points.…”
Section: Related Workmentioning
confidence: 99%
“…To improve the efficiency of water distribution and to reduce waste related to leaks, a sensor network can be used to execute those analyses with precision and in an autonomous way. Some research and development can be found in both the academic and industrial worlds, ranging from expansive fixed systems that use ultrasonic clamps to analyze real-time water flow, such as [11], to low-cost solutions found in the academic world, such as [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%